Vulnerability of soil and water in Mediterranean agro-forestry systems - Duarte, A.C. (2017)
The study watershed is located within the Idanha Irrigation Scheme, Portugal. A hydrological and water quality station was installed at the outlet of the catchment. The AnnAGNPS model was applied in this study, and afterwards it was calibrated and validated to the conditions in the study catchment. The antecedent soil moisture conditions play an important role for rapid runoff and flash flooding. Relative Water Supply (RWS) is always bellow the unity value and sometimes below the value 0.5. Sometimes in very dry years, like the year 2004-2005 (302 mm), a runoff coefficient is equal to 0.40. Spatial distribution of runoff was primarily influenced by topography and soil management, which is common in Mediterranean agricultural systems, namely in grain crop systems such as oats and wheat. The simulation of spatial distribution of nitrate load shows a dependence of the spatial distribution of runoff, due to its high solubility. Spatial distribution of soil erosion by water indicates that the process does not depend directly on the runoff distribution in the catchment. Therefore, soil erosion is greatly influenced by deficient land cover whenever erosivity of rainfall is strong. Phosphorus losses were less than nitrate losses, due to their lower water solubility and mobility in soil.